Novel Method for Optimizing Traffic Police Manpower by Standby and Patrol - yang, yanqun; Miao, Mingyue; Easa, Said; Chen, Jianying; Zhang, Jun; Li, Qiang (IJRDO - Journal of Applied Management Science, 2021)
The purpose of this research paper is to find out a quantitative method that could assist traffic police department with determining minimum patrol and standby staffing and optimizing shift schedule to meet current performance benchmarks. The average events rate reflects the overall traffic situation over a certain period of time. By Fault Tree Analysis (FTA) method, average events occurrence rate could be expressed by a linear equation, which combines the number of traffic accidents, congestion events, and serious violation events with their key importance coefficients. Next, the number of patrol team and the sum of the minimum number of patrol and standby police could be obtained by applying Queueing model and Poisson Distribution model, based on comparing and analyzing both models by average events occurrence rate. These variables mentioned will be used to establish constraint equations in Integer Programming (IP) model. Finally, it is provided to the traffic police detachments or stations, especially those consisted of patrol police and clerical police, to a relatively simple and quantitative way to optimize police resources based on traffic conditions of their precinct.